How free is prudent behavior? - Sensen, Oliver (Studia Kantiana, 2023)
We ordinarily believe that we have the capacity to freely act otherwise. If you have a choice between two desserts, for instance, we believe that in a deep metaphysical sense this decision is up to you. Given the same desires, information, circumstances, biological makeup, and past experiences, you can decide one way or the other. We believe that the decision is not causally pre-determined, and that one could not predict with certainty how an agent will behave. It is not clear, however, whether Kant upholds this conception of freedom. On one reading of his texts, only morally good actions can be free (cf. GMS 4:446f). This led to the charge, made famous by Reinhold and Sidgwick, that we cannot be blamed for immoral actions (cf. Reinhold 1792; Sidgwick 1874, 58). For if only moral actions are free, and if praise and blame presuppose that we were free and responsible, then one cannot be blamed for an immoral action. In this sense Kant seems to be saying that only acting morally is a capacity, but failing to do so merely the lack of a capacity (cf. MS 6:226).